2009
DOI: 10.1063/1.3080549
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of atomic and electronic structure of neutral Si6Om (m=1–11) clusters

Abstract: In this paper we found the most stable structures of silicon-oxide clusters of Si 6 O m ͑m =1-11͒ by using the genetic algorithm. In this work the genetic algorithm uses a semiempirical energy function, MSINDO, to find the best cluster structures of Si 6 O m ͑m =1-11͒. The best structures found were further optimized using the density functional theory. We report the stable geometries, binding energies, lowest unoccupied molecular orbital-highest occupied molecular orbital gap, dissociation energies for the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
4
16
0
Order By: Relevance
“…The Si 6 O isomers are, however, most stable with an O atom on the edge of a low-energy isomer of the Si 6 cluster. Our numerical results are in good agreement with earlier calculations of Si 6 O 24 and Si 6 B. 51 Furthermore, to the best of our knowledge, we have found a new lowest-energy structure for the Si 6 N cluster (d0, Fig.…”
Section: A Predicted Structuressupporting
confidence: 91%
See 1 more Smart Citation
“…The Si 6 O isomers are, however, most stable with an O atom on the edge of a low-energy isomer of the Si 6 cluster. Our numerical results are in good agreement with earlier calculations of Si 6 O 24 and Si 6 B. 51 Furthermore, to the best of our knowledge, we have found a new lowest-energy structure for the Si 6 N cluster (d0, Fig.…”
Section: A Predicted Structuressupporting
confidence: 91%
“…Whereas an enormous amount of theoretical work on small doped silicon clusters is available (e.g., ref. 12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], only a few experiments have been reported in the gas phase. 8,14,[35][36][37][38] By sequential doping of silicon clusters with carbon atoms, i.e., for Si m C n with m + n = 6, we recently observed a systematic transition from one-dimensional geometries for pure C 6 to three-dimensional structures for pure Si 6 .…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The energies of 10 best structures for each composition were refined using the GAUSSIAN code 36 with the B3LYP/6-311+G(2d,p) approach. 37 Comparison of our results with earlier publications 4,6,10,[26][27][28][30][31][32][33] showed that 101 optimal structures of Si n O m clusters were correctly reproduced by us, 17 better ones were found, and 197 clusters were studied for the first time to our best knowledge (see table 1 in SI). Fig.…”
supporting
confidence: 74%
“…315 cluster compositions). We note that the earlier investigations of Si n O m were either done for relatively small clusters (n ≤ 7) 6,26,28,30,31 or focused on stoichiometric compounds (SiO) n or (SiO 2 ) n . 4,10,27,32,33 Even for these compounds it is often seen that newer papers report lowerenergy structures than the older ones.…”
mentioning
confidence: 99%
“…reproduce experimental values of properties of neutral and ionic Si n O m species and also the results of higher-level calculations. [1,3,[8][9][10] Møller-Plesset second-order perturbation theory (MP2) has been used to perform intrinsic reaction coordinate (ICR) and energy barrier calculations of several Si n O m clusters reactions, obtaining results in reasonable agreement with coupled cluster methods. [11] For the PES calculations performed in this work, scans at the MP2/6-31G(d) level of theory (including all electrons) were carried out at specific locations of the PES, to obtain more accurate energy values of possible transition states and barriers.…”
Section: Original Articlesmentioning
confidence: 99%